Dos acordos globais às interpretações locais sobre agricultura sustentável: tradução e implementação do Plano e do Programa ABC - Leticia Chechi; Catia Grisa (Confins)
This paper aims to discuss how international climate agreements were translated by the Brazilian agribusiness actors in the construction of the Sectorial Plan for Mitigation and Adaptation to Climate Change for the Consolidation of a Low Carbon Economy in Agriculture (ABC Plan), and how it was implemented in the states of Minas Gerais and Rio Grande do Sul, through the ABC Program. For that, 70 actors linked to the construction and implementation of these actions were interviewed, and was utilized the policy translation and implementation approaches. The paper demonstrates that the ABC Plan construction involved a certain advance translation of the ideas from the international to the national context. Interpreted as an opportunity to re-signify the Brazilian agriculture, agribusiness actors defined a strategy in advance and attended in the COP15 with a structured policy proposal for low-carbon agriculture. Diverging of the unidirectional policy transfer, the Plan and the ABC Program resulted of a process of two-way translation from the international to the national level, strategically guided by Brazil. After being “translated” into the national context, the ABC Plan and Program were (re)translated during its implementation, when reaching local spaces. If the ideas of reducing greenhouse gases (GHG) emissions were present during the ABC Plan and Program formulation, they do not find any correspondence in the interpretations and actions of street-level bureaucrats. They interpret the Program as another credit line, pointing out formal and administrative issues that discourage the policy access. It is observed, therefore, an interpretive distance between the ideas on the global scale and their translations into national and local scales.